The Sphingosine 1‐Phosphate Analogue FTY720 Alleviates Seizure‐induced Overexpression of P‐Glycoprotein in Rat Hippocampus. Issue 1 (13th March 2018) - Gao, Fei; Gao, Ying; Meng, Fangling; Yang, Chunmei; Fu, Jiangfeng; Li, Yajun
Abstract: Overexpression of P‐glycoprotein (P‐gp) in the brain is an important factor leading to drug‐resistant epilepsy. Clinical use of P‐gp inhibitors is limited by their systemic toxicity. In this study, we tested the hypothesis that FTY720, a sphingosine 1‐phosphate (S1P) analogue used for treating multiple sclerosis, modulates the up‐regulation of P‐gp and improves brain delivery of phenytoin (PHT) through S1P receptor 1 in the hippocampus of a pilocarpine‐induced rat model of status epilepticus (SE). We administered vehicle, FTY720 or FTY720+ W146 (an S1P receptor 1 antagonist) to SE rats. Forty‐eight hours after SE, we dissected the hippocampus and measured P‐gp expression, NF‐κB activity and levels of inflammatory mediators (TNF‐α and COX‐2) by Western blotting and enzyme‐linked immunosorbent assay. We also measured hippocampal and plasma concentrations of PHT 30, 60, 90, 120 and 180 min. after an intraperitoneal injection of PHT (50 mg/kg) 48 hr after SE, using microdialysis and high‐performance liquid chromatography. FTY720 alleviated the overexpression of hippocampal P‐gp in SE rats and reduced NF‐κB activity and TNF‐α and COX‐2 expression, and W146 blocked the effects of FTY720. Furthermore, SE rats that received FTY720 showed significantly greater hippocampal extracellular PHT concentrations than those that received vehicle, and W146 abolished this effect. Our results suggest that FTY720 alleviates seizure‐induced overexpression of P‐gp by inhibiting S1P receptor 1‐mediated inflammation in rat hippocampus and improves PHT delivery to brain. FTY720 shows potential as an adjuvant therapy for drug‐resistant epilepsy.